TITIK TEMU EPISTEMOLOGI BARAT DAN ISLAM - Muzakki, Akhmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
Beside ontology and axiology, the object of philosophy of science is epistemology that discusses the truth of, the method of finding, and the reality of science. ]n epistemology, there are many schools discussing the process of finding the truth of science, such as, rationalism, empiricism, criticism, phenomenology, positivism, pragmatism etc. In the trilogy of Islamic teachings, that is, iman (faith), Islam, and ihsan (perfection), generally sciences in Islam can be classified into three branches of study: (1) Ilmu Tauhid (theology), this science makes use of intellectual ability or logic (burhani method) which is epistemologically identical with rationalism; (2) Ilmu Fiqh (Islamic laws), this frequently uses bayani method, that is, inductive and deductive framework, in epistemology this method is called empiricism; (3) Ilmu Tasawwuf (mysticism), this science uses the power and purity of heart, it is called irfani method that is similar to phenomenology in Western philosophy of science. Therefore, epistemologically, basically the development of sciences in Islam cannot be separated from Western epistemological schools, that is, rationalism, empiricism, and phenomenology as well.